Potential Clinical Value of Pretreatment De Ritis Ratio as a Prognostic Biomarker for Renal Cell Carcinoma - Li, Jinze; Cao, Dehong; Peng, Lei; Meng, Chunyang; Xia, Zhongyou; Li, Yunxiang; Wei, Qiang (Frontiers in Oncology, 2021)
Background: We performed this meta-analysis to explore the prognostic value of the pre-treatment aspartate transaminase to alanine transaminase (De Ritis) ratio in patients with renal cell carcinoma (RCC). Methods: PubMed, EMBASE, Web of Science, and Cochrane Library were searched to identify all studies. The hazard ratio (HR) with a 95% confidence interval (CI) for overall survival (OS) and cancer-specific survival (CSS) were extracted to evaluate their correlation. Results: A total of 6528 patients from 11 studies were included in the pooled analysis. Patients with higher pre-treatment De Ritis ratio had worse OS (HR = 1.41, P < 0.001) and CSS (HR = 1.59, P < 0.001). Subgroup analysis according to ethnicity, disease stage, cut-of value, and sample size revealed that De Ritis ratio had a significant prognostic value for OS and CSS in all subgroups. Conclusions: The study suggests that elevated pre-treatment De Ritis ratio is significantly correlated with worse survival in patients with RCC. Pre-treatment De Ritis ratio may serve as a potential prognostic biomarker in patients with RCC, but further studies are warranted to support these results.